Analysis of the Influence of Smm, Ocr, and Im on the Brand Image of Fashion Products in Tiktok Shop - Fitria Ika Agustina; Amiruddin Kalbuadi; Dini Milhiani (Business Management, 2025)
This research aims to determine the influence of social media marketing, online customer reviews and influencer marketing on brand image. This type of research uses quantitative research. Data collected in this research used a questionnaire distributed via a Google Form link. The population or sample in this study was 85 respondents. Respondents were taken from students who had purchased fashion products at the TikTok shop. Data were processed using multiple linear analysis, t test and f test with the help of SPSS. The results of this research show that the t test that has been carried out on the social media marketing variable on brand image partially has a significant effect. The online customer review variable on brand image partially has a significant effect. The influencer marketing variable on brand image partially has a significant effect. Simultaneously, all variables, namely social media marketing, online customer reviews and influencer marketing, have a positive and significant effect on brand image. Meanwhile, the results of the last test, namely the online customer review variable, show a dominant influence on brand image. The conclusion of this research shows that the variables of social media marketing, online customer reviews and influencer marketing have a positive and significant effect on the brand image of fashion products in the TikTok shop.